Model Pengembangan Kurikulum Berbasis Madrasah Digital di Mi Mambaul Ulum Dagan Solokuro Lamongan - Leni Fitrotul Awwaliyah (Yayasan Mutiara Hati Moeslem, 2025)
The aim of this research is to describe the Digital Madrasah-Based Curriculum Development Model at Mi Mambaul Ulum Dagan Solokuro. The method used in this research is descriptive qualitative with a case study type. Data collection techniques include observation, interviews and documentation. Data analysis was carried out using the Miles & Huberman theory, which includes data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the research show that in curriculum development the curriculum development model is implemented by collaborating between the Skillbeck model and D.K. Wheeler by applying goal formulation, program preparation, learning system implementation, learning strategies and evaluation The supporting factors for curriculum development are the existence of a special team in curriculum development, adequate infrastructure for students, giving rewards to students, while the inhibiting factors are the existence of teachers who cannot fully understand the new curriculum, namely the independent curriculum, lack of approach from students. , lack of order in the learning process.